2020
DOI: 10.3390/polym12091926
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Antibacterial Gelatin/Sodium Alginate Sponges and Their Antibacterial Activity

Abstract: In the present study, sponges with the antibiotic tetracycline hydrochloride (TCH) loaded into alginate incorporated with gelatin (G/SA) were fabricated. The G/SA sponges were characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and thermogravimetric (TG) analysis. G/SA sponges show a three-dimensional network structure with high porosity. An excellent swelling behavior and a controlled TCH release performance are observed from G/SA sponges. Moreover, they exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…However, the main disadvantages of gelatin are its low thermal stability and insufficient mechanical properties. Gelatin is used, inter alia , as a dressing material, in the production of soft and hard capsules, drug delivery systems, and in tissue engineering [ 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Biopolymers Used To Prepare Hydrogelsmentioning
confidence: 99%
“…However, the main disadvantages of gelatin are its low thermal stability and insufficient mechanical properties. Gelatin is used, inter alia , as a dressing material, in the production of soft and hard capsules, drug delivery systems, and in tissue engineering [ 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Biopolymers Used To Prepare Hydrogelsmentioning
confidence: 99%
“…The bands around 1025 cm − 1 are the C-O-C bonds as identi ed in sodium alginate as well 34 . Furthermore, the peak at about 1415-1460 cm − 1 is attributed to COO-, which is linked to the alginate hydrogen 35 . The peak at 1526 cm − 1 is due to the N-H group of amide II and that observed at 1266 cm − 1 is associated with the N-H group of amide III of gelatin 35,36 .…”
Section: Rna Extraction and Real Time-pcrmentioning
confidence: 99%
“…Furthermore, the peak at about 1415-1460 cm − 1 is attributed to COO-, which is linked to the alginate hydrogen 35 . The peak at 1526 cm − 1 is due to the N-H group of amide II and that observed at 1266 cm − 1 is associated with the N-H group of amide III of gelatin 35,36 . The peak appeared at 1625 cm − 1 is the characteristic of-CONH 2 group, indicating that the negative group of alginate is probably linked with positive load of gelatin 37 .…”
Section: Rna Extraction and Real Time-pcrmentioning
confidence: 99%
“…The in vitro studies showed that the TCH-loaded sponges exhibited a controlled release profile with good antibacterial efficacy against E. coli ATCC25, ATCC922, as well as B. subtilis ATCC 9372 and S. aureus ATCC 6538. The fabricated gelatin-sodium alginate sponges are potential wound dressings for treating bacteria-infected wounds [ 73 ].…”
Section: Gelatin-based Hybrid Wound Dressingsmentioning
confidence: 99%